Sodium intake and its association with knowledge, attitudes and practices among health sciences students in Universiti Sultan Zainal Abidin (Unisza) - Che Suhaili, Che Taha; Sakinah, Harith; Nur Hayati Nisar, Ahmad (Penerbit Universiti Sultan Zainal Abidin, 2020)
High salt intake is a major risk factor of hypertension and cardiovascular disease. Improving knowledge, attitudes and practices (KAP) in salt intake among population is one of the key components of salt reduction strategies. This study aimed to measure the mean intake of dietary sodium among health sciences students in Universiti Sultan Zainal Abidin (UniSZA), assess the knowledge (K), attitudes (A) and practices (P) on sodium intake and to determine the dietary sodium intake and its relationship with KAP. A total of 402 undergraduate students with the mean age of 21.0 ±1.22 years old were recruited in this cross-sectional study consisting of 44 men (10.9%) and 358 women (89.1%) using convenience sampling. Socio-demographic data were obtained using selfadministered questionnaires. Anthropometric data of height and weight were measured. Sodium intakes were estimated using Food frequency Questionnaire (FFQ) while KAP was measured using well validated questionnaires adapted from Institute for Public Health. The mean intake of sodium among respondents was 2617.8 ± 1862.98 mg/day, exceeded the recommendation. Major contributor to salt intake was from the food groups of cooked grains followed by sauces and fast food. The knowledge of most respondents was good with 98% of them had knowledge on serious health problems contributed by high salt intake, especially blood pressure (75.1%). More than half of the respondents felt that lowering salt intake was very important (61.7%). Respondents also reported frequent controlling of sodium intake (65.9%) by minimizing processed food intake (83.4%). However, no significant association was found between KAP on dietary sodium intake (p>0.05). Nevertheless, undergraduate students with nutrition related courses were found to have better knowledge and practices (p<0.05) compared to those with non-nutrition related courses. Acknowledging that this study limited to health sciences students in UniSZA, future studies encompassing students from other universities are recommended in order to represent the Malaysian university populations KAP on sodium intake.